HUBUNGAN PENGETAHUAN IBU TENTANG OBESITAS BALITA DENGAN KEJADIAN OBESITAS PADA BALITA DI NAGARI KOTO RAJO KAB. PASAMAN TAHUN 2015 - Fransiska, Mellia; Rahmadani, Melda (Jurnal Kesehatan - STIKes Prima Nusantara, 2017)
Liver cirrhosis is often found in old age, the disease can cause death if not treated immediately. Data from the Provincial Health Office in Padang, liver cirrhosis ranks 17th in 2015 ie 213 cases. The number of cases of liver cirrhosis at IbnuSina Islamic Hospital BukittinggiYarsi West Sumatera in 2016 (January-December) has reached 30 cases. The purpose of the study was to determine the risk factors of liver cirrhosis incidence at Ibnu Sina Hospital BukittinggiYarsi West Sumatra. The research design used was analytical research using "Case-Control" study approach. The study population was 21 cases with 42 samples, 21 cases, and 21 controls, using Simple Random Sampling technique in the case group and Purposive Sampling in the control group. The research started from March to September 2017. The analysis used was Univariate and Bivariate analysis using Chi-Square. The results showed that there was no correlation between age with the incidence of cirrhosis of the liver with value (p = 1,000), there was a correlation between drug use and the incidence of cirrhosis of the liver with value (p = 0.0001), there was a relationship between Hepatitis B and C History with Liver Cirrhosis with value (p = 0.0001), there was no correlation between the Habits of Alcohol Consumption and the incidence of Liver Cirrhosis with value (p = 0.536). The conclusion of this study that drug use factor and history of hepatitis B and C have a significant relationship with the incidence of liver cirrhosis.